Haji Sebagai Laku Revolusioner: Tinjauan Kepustakaan - Muhammad Nashirulhaq (SIASAT, 2018)
This article argues that the hajj as a religious rite, in the past, has the potential to foster progressive awareness and drive socio-political transformation for Muslims, especially in Indonesia. This inevitably raises a new question: can the pilgrimage now be expected to play a role in driving change for Muslims who are still entangled in the bonds of neo-colonialism, neo-imperialism and neo-liberalism.